In situ formation and solid-state oxidation of a triselenane NSeN-pincer MOF. Issue 8 (6th January 2020) - He, Shichao; Allemond, Laynee L.; Dunning, Samuel G.; Reynolds, Joseph E.; Lynch, Vincent M.; Humphrey, Simon M.
Abstract : Controlled partial decomposition of 2-selenonicotinic acid in the presence of Co 2+ or Ni 2+ resulted in the in situ formation of an unusual MOF based on triselenane ligands (RSeSeSeR) coordinated to M 2+ centers as NSeN-pincers. Abstract : Controlled partial decomposition of 2-selenonicotinic acid in the presence of Co 2+ or Ni 2+ resulted in the in situ formation of an unusual MOF based on triselenane ligands (RSeSeSeR) coordinated to M 2+ centers as NSeN-pincers. Post-synthetic oxidation by treatment with aqueous H2 O2 facilitates its solid-state conversion into a RSeO2 − molecular coordination complex, which was tracked via powder X-ray diffraction studies and by single-crystal structural resolution of the final product.